Academic Supervision in Islamic Boarding Schools: Challenges, Gaps, and Strategies for Educational Quality - Safitri Cristina Sari; Ahmad Azkal Azkiya' (International Journal of Multidisciplinary Research of Higher Education, 2026)
This study aims to analyze the gaps in the implementation of academic supervision in Islamic boarding schools by examining the current reality, implementation barriers, and potential strategies for improvement. This study employs a descriptive qualitative method using a case study design, conducted over a three-month period from September to November 2025 at a junior high school in Indonesia. This study focuses on revealing the practices of academic supervision, the implementation barriers faced, and their implications for the learning process and students’ academic achievement in the Islamic Boarding Schools environment. Data sources were obtained from ten informants, consisting of one school principal, one vice principal for curriculum, one school supervisor, four core subject teachers, two parents, and one school committee representative. Data analysis was conducted using a thematic matrix and comparative tables to map the gaps between academic supervision standards and actual practices in the field. The research findings also reveal variations in student academic achievement influenced by inconsistent supervision, with results ranging from improvement to stagnation and even a decline in performance. The findings indicate that these disparities stem from weak planning, a lack of coordination, and insufficient training for supervisors. The findings and opinions in this study offer practical and theoretical implications for strengthening the governance of academic supervision in Islamic boarding schools, particularly as a foundation for formulating more systematic, collaborative, and culturally contextual supervision policies aimed at improving the quality of learning and the consistency of students’ academic achievement.